Transcriptomic definition of molecular subgroups of small round cell sarcomas. Issue 1 (30th March 2018) - Watson, Sarah; Perrin, Virginie; Guillemot, Delphine; Reynaud, Stephanie; Coindre, Jean‐Michel; Karanian, Marie; Guinebretière, Jean‐Marc; Freneaux, Paul; Le Loarer, François; Bouvet, Megane; Galmiche‐Rolland, Louise; Larousserie, Frédérique; et al.
Abstract: Sarcoma represents a highly heterogeneous group of tumours. We report here the first unbiased and systematic search for gene fusions combined with unsupervised expression analysis of a series of 184 small round cell sarcomas. Fusion genes were detected in 59% of samples, with half of them being observed recurrently. We identified biologically homogeneous groups of tumours such as the CIC ‐fused (to DUX4, FOXO4 or NUTM1 ) and BCOR ‐rearranged ( BCOR – CCNB3, BCOR – MAML3, ZC3H7B–BCOR, and BCOR internal duplication) tumour groups. VGLL2 ‐fused tumours represented a more biologically and pathologically heterogeneous group. This study also refined the characteristics of some entities such as EWSR1–PATZ1 spindle cell sarcoma or FUS–NFATC2 bone tumours that are different from EWSR1–NFATC2 tumours and transcriptionally resemble CIC ‐fused tumour entities. We also describe a completely novel group of epithelioid and spindle‐cell rhabdomyosarcomas characterized by EWSR1– or FUS–TFCP2 fusions. Finally, expression data identified some potentially new therapeutic targets or pathways. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.